2010
DOI: 10.1164/rccm.200906-0959oc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of a Diagnosis of Idiopathic Pulmonary Fibrosis

Abstract: Clinical data may be used to predict a diagnosis of IPF over other IIPs. Validation of these data with a prospective study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(172 citation statements)
references
References 29 publications
8
155
4
5
Order By: Relevance
“…When IPF is the underlying cause of death, it may be misclassified or misdiagnosed, depending on the extent of diagnostic work-up prior to death, and also due to coding irregularities, and our validation cohort analysis provides evidence that cases of confirmed IPF are sometimes coded as 'unspecified' (ICD-10 code J84.9). ICD-10 code J84.1 is the most specific code for IPF, and this is supported by it being less common in younger patients, with higher rate ratios for increasing age, consistent with IPF being a disease of older people (16,17). However, using J84.1 may miss these unspecified cases and so may underestimate mortality.…”
Section: Discussionmentioning
confidence: 95%
“…When IPF is the underlying cause of death, it may be misclassified or misdiagnosed, depending on the extent of diagnostic work-up prior to death, and also due to coding irregularities, and our validation cohort analysis provides evidence that cases of confirmed IPF are sometimes coded as 'unspecified' (ICD-10 code J84.9). ICD-10 code J84.1 is the most specific code for IPF, and this is supported by it being less common in younger patients, with higher rate ratios for increasing age, consistent with IPF being a disease of older people (16,17). However, using J84.1 may miss these unspecified cases and so may underestimate mortality.…”
Section: Discussionmentioning
confidence: 95%
“…Recently it has been shown that in patients without honeycombing in HRCT, older age and modest amount of fibrosis, such as reticular changes are highly predictive of IPF. However, it should be stressed that these findings need further confirmation in multicentre prospective studies [78].…”
Section: Is Bal Useful In the Diagnosis And Management Of Ilds?mentioning
confidence: 92%
“…In the absence of additional CTD features, ILD patients with lowtitre ANA and/or RF likely do not require referral to a rheumatologist, particularly if the onset of ILD is after the age of 65 years. 29 Conversely, referral to a rheumatologist should be considered in patients with suggestive clinical features, specific autoantibodies, or high titre ANA ( 1:320) and/or RF ( 60 IU/mL). 18,19 Similarly, a rheumatology referral should be considered in patients that meet criteria for IPAF (see Reference 19 for IPAF criteria).…”
Section: High Resolution Computed Tomographymentioning
confidence: 99%